All history is local history. Een pleidooi voor glocalisering van lokale en regionale geschiedenis - Bijsterveld, Arnoud-Jan; Mol, Hans (Studies over de sociaaleconomische geschiedenis van Limburg, 2018)
All history is local history. A plea for the glocalization of local and regional history Regional and local history go back a long time in the various provinces of the Netherlands. Focusing on the provinces of Friesland, Noord-Brabant, and Limburg this article shows how after a long and slow development, scientific historiography there only developed after the 1950s, leading to the establishment of research institutes and funded chairs. Nevertheless, the rise of the heritage field, the demand for valorization, and budget cuts may threaten their positions. Yet, doing regional history should be an integral part of national history and is ever more relevant in a globalizing world, which demands for glocalization, that is, the interaction of globalization with the local living environments and their idiosyncratic local structures, cultures, and histories.